2021
DOI: 10.21873/cgp.20288
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of the Growth Inhibitory Effects of Paclitaxel on Gefitinib-resistant Non-small Cell Lung Cancer Cells

Abstract: Background/Aim: Coronavirus disease 2019 (COVID-19) poses a great challenge for the treatment of cancer patients. It presents as a severe respiratory infection in aged individuals, including some lung cancer patients. COVID-19 may be linked to the progression of aggressive lung cancer. In addition, the side effects of chemotherapy, such as chemotherapy resistance and the acceleration of cellular senescence, can worsen COVID-19. Given this situation, we investigated the role of paclitaxel (a chemotherapy drug) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Recent reports also show that low-concentration PTX can kill cancer cells indirectly through inhibiting the proliferation of human endothelial cells and reducing the expression of angiogenesis markers, such as VEGF, TGFA and FGF, to lessen the input of nutrition [ 8 ]. Apoptosis is also one of the important ways in which PTX exerts its antineoplastic effect, but the signaling pathways involved are distinct in different cancer cells [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports also show that low-concentration PTX can kill cancer cells indirectly through inhibiting the proliferation of human endothelial cells and reducing the expression of angiogenesis markers, such as VEGF, TGFA and FGF, to lessen the input of nutrition [ 8 ]. Apoptosis is also one of the important ways in which PTX exerts its antineoplastic effect, but the signaling pathways involved are distinct in different cancer cells [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTX exerts its cytotoxic effect by arresting mitosis through microtubule stabilization or reactive oxygen species (ROS)‐mediated DNA damage, resulting in cellular apoptosis. [ 26 ] CHEK2 is a core component of the DNA damage response in tumor cells, phosphorylating the downstream kinase CDC25 and preventing damaged cells from mitosis to provide extra time for DNA repair. [ 27 ] Next, We detected the expression of p‐CHEK2/CHEK2 and its downstream targets, including cell cycle related protein CDC25A, CDC25B, and CDC25C.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with the results of a previous study that showed that PTX-induced ROS accumulation stimulates the expression of HIF-1α and activates caspase-3 signaling to promote apoptosis in prostate cancer cells [ 27 ]. Notably, PTX can bind to β-tubulin and prevent the dissociation of microtubules, blocking cell cycle progression, and also inducing apoptosis and senescence through the distinct signaling pathways involved in different cancer cells [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…HMGA2 overexpression has been and is associated with poor prognosis, low survival rates, and advanced stage in various types of human cancer. HMGA2 protein is an independent indicator of shorter patient survival time and tumor progression in several cancers, including gastric cancer, oral squamous cell carcinoma, and bladder cancer [ 28 ]. The mouse that had the intestine-specific Hmga2 overexpression accelerated azoxymethane (AOM)/dextran sodium sulfate (DSS) carcinogen-induced tumor development [ 30 ], suggesting an important role of HMGA2 in colorectal cancer development.…”
Section: Discussionmentioning
confidence: 99%